An early method for the technical diagnosis of pin-on-disk tribometers by reference friction measurements in EHL conditions. (15th December 2020) - Goti, Edoardo; Mazza, Luigi; Mura, Andrea; Zhang, Bin
Highlights: A novel reference test procedure is proposed for the pin-on-disc tribometers technical diagnosis. The EHL condition is exploited to obtain stable and highly repeatable friction curves. A user-friendly lubricated test setup is put in place in order to fit industrial applications. Measurements are performed with 2 tribometers in 2 laboratories, then analyzed and compared. Abstract: Reference tests are widely used to calibrate scientific instruments but are potential candidate to establish technical diagnosis procedures for scientific instruments too. A reference test is currently lacking in tribology. Though, it would allow users to check that tribometers are properly working and may also form a yardstick for cross-laboratory comparative studies. In this paper two easy-to-use reference testing procedures for the diagnosis of commercial pin-on-disc tribometers are established resorting to a special no-wear test setup in EHL conditions. Several tests were carried out with two tribometers and two commercial oils, and both standardized testing modes were investigated: unidirectional-rotating and linear-reciprocating mode. The friction curves from more than 350 tests were analyzed to generate meaningful statistics supporting the robustness of these procedures. The test setup proved to be suited to the task since the summary of the results showed an excellent repeatability of friction curves concerning appearance and average values.